2019
DOI: 10.1016/j.arth.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Use of Closed Incisional Negative Pressure Wound Therapy After Revision Total Hip and Knee Arthroplasty in Patients at High Risk for Infection: A Prospective, Randomized Clinical Trial

Abstract: Background: Continuous wound drainage after arthroplasty can lead to the development of a periprosthetic joint infection. Closed incisional negative pressure wound therapy (ciNPWT) has been reported to help alleviate drainage and other wound complications. The purpose of this prospective randomized controlled trial is to compare the use of ciNPWT with our standard of care dressing in revision arthroplasty patients who were at high risk to develop wound complications. Methods: A total of 160 patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 38 publications
1
94
0
Order By: Relevance
“…Because patients with certain risk factors are frequently associated with SSCs, a variety of dressing materials were applied to prevent SSCs. 4,12,13 However, the proper indication and the best choice of dressing materials for wound management after THA and TKA still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Because patients with certain risk factors are frequently associated with SSCs, a variety of dressing materials were applied to prevent SSCs. 4,12,13 However, the proper indication and the best choice of dressing materials for wound management after THA and TKA still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our meta-analysis defined complication as minor or major. Some studies indicated that iNPWT had an effect on decreasing complications but there were some studies reporting the opposite efficacy [18,21,23]. In this meta-analysis, no difference in overall, minor and major complications were found after TJA.…”
Section: Discussionmentioning
confidence: 74%
“…However, the effect of application of diverse wound dressings remain unclear. Some present studies found that iNPWT has an advantage on wound healing [5,21]. A previous systematic review [22] evaluating the prophylactic use of iNPWT for wound complications in several surgical fields such as laparotomy for abdominal, coronary arteries bypass grafting, and lymphadenectomy.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The successful application of ciNPT on clean, closed wounds has been reported in a broad spectrum of patients and operative interventions resulting in positive clinical results in a majority of the RCTs identified in the literature search ( Table 2) [11][12][13][14][15][16][17][18][19]. Similarly, rates of SSIs, surgical site complications, readmissions, and/or reoperations were reduced in patients receiving ciNPT compared to historical control populations [20][21][22][23][24][25].…”
Section: Literature Searchmentioning
confidence: 95%